Radiological Evaluation of Innominate Bone for Age Estimation: A Cross Sectional Study from Central India - Ninad Nagrale1 , Swapnil Patond2 , Ranjit Ambad3, Nandkishor Bankar3 , Karan Jain4 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Age is cardinal in both civil & criminal cases as it not only affects the way an individual is treated, both incourt and with regards to bail, but it also influences the defence under Indian Penal system. The defence forchildren is easier to establish than that for an adult. This study focuses on investigating the relationship betweenthe stage of fusion of secondary ossification centres of innominate bone & biological age in Chhattisgarhpopulation. This study was carried out in 140 healthy subjects (70males and 70 females) aging from 17 to 24years. The obtained results revealed that the complete fusion of both epiphyses of innominate bone is seenat 21-22 years. Comparatively, females were developing epiphysealunion at a younger age than their malecounterparts. Results also suggest that the age of epiphyseal fusion at iliac crest & ischial tuberosity is foundto vary greatly all over the India, indicating the need for separate standards for separateregions.